The Development of Children’s Story Book Media Based on Local Natural Resources to Support the Early Counting Mathematics Program for Kindergarten Level - Darnis, Syefriani (TADARUS, 2019)
Learning media has a contribution in increasing student activity and motivation in learning. The use of the right teaching media in learning process can arouse desire, generate motivation and stimulate new learning activities. The more intensive the learning  experience by students, the higher of the quality learning process itself. Student involvement is based on motivation and high interest from the students in participating in the learning process, and also from the teacher’s side is required to master the use of various types of media and learning strategies. For this reason, it is necessary to think about alternative learning media that are fun and appropriate for students. One of the media used in learning mathematics is a storybook based on Local Natural Resources  whose contents are close to the lives of children. Its need creative thinking and innovation to create local cultural outcomes that are packaged so that they are accepted and studied globally. Environmental preservation efforts such as raising the potential of local nature can make the younger generation have responsibility for their environment. Preservation of living natural resources by reprinting and making new natural resources can not be the thing that young people are interested in. One effort to conserve local natural resources is through learning resources in education which hopes to provide an understanding of the results of local natural resources wealth to the next generation. By introducing natural potential through learning activities by streamlining the function of storybook media in learning for children. The use of media should be a part of our attention as a means of preserving local natural potential in the world of education. Therefore, it is necessary to establish learning media that can be accepted by the current generation by revitalizing local potential in the era of globalization. The purpose of this research is to develop the local natural resources from Dukuh Samiran , Kecamatan Selo, Boyolali, Central Java,  as supporting the early counting mathematics program. The research applied was Research and Development. The subjects of this study was 20 children of Group of Kindergarten B.  Keyword : Learning  media, Mathematics,  Local Natural Resources, early counting